Can Home-Based Care for Disabilities Foster Social Resilience? Implications for Research and Future Directions - Rd Ahmad Buchari (Dealings Foundation Institute, 2024)
This research aimed to identify, review, and study the development of scientific publication trends regarding home-based care for disability issues worldwide. This study provides scientific guidance and recommendations for the development of home-based disability care research to create social resilience. The method of this study is a systematic review and meta-analysis through the PRISMA protocol. The findings of this study evaluated the literature review taxonomy through two specific analyses: (1) this study explores the evolution of the research literature from year to year across the three databases on home-based disability care in the last 10 years; and (2) this study investigates whether home-based disability care research has a positive impact on addressing issues of social change, inclusive development, increased sustainability, increased community resilience, and improved quality of life. This research contributes to helping researchers explain, support, and expand the emergence of new theories from the results of research on disability and social issues.